Academic System for Teacher–Parent Monitoring of Student Learning Progress - Gilang Estu Saputra; Tri Hidayat, Ahmad (Kirana Publisher (KNPub), 2025)
This study develops a Web-Based Academic Information System (SIA) as an integrated communication platform between teachers and parents to monitor student learning progress at SD Negeri 3 Gunungwuled, Purbalingga. The research addresses delayed academic information flow caused by manual, paper-based reporting and inconsistent communication channels. Using a user-centered, iterative design and development approach, the system implements real-time grade input, attendance monitoring, learning progress reports, and a responsive interface accessible to both teachers and parents. Functional and usability testing with representative users demonstrated improved accessibility, reduced information delays, strengthened two-way communication, and a more efficient monitoring workflow within daily school operations. The system’s architecture supports timely data entry by teachers and instant visibility for parents, ensuring alignment on student performance, attendance patterns, and targeted interventions. Results indicate the platform effectively replaces fragmented manual processes with a coherent digital workflow, enhancing transparency and decision-making. The study concludes that the SIA enables a practical digital transformation in academic management at the primary school level and contributes a replicable model for similar institutions seeking to modernize academic information services and parent–teacher communication.